Carcass and meat traits of lambs fed by-products from the processing of oil seeds - doi: 10.4025/actascianimsci.v35i4.20403 - Santos, Viviane Correa (2013)
We evaluated the effect of adding by-products from the processing of oil seeds in the diet of lambs on the carcass and meat traits. Twenty-four non-castrated weaned male Santa Inês lambs with approximately 70 days of age and initial average weight of 19.11 ± 2.12 kg were distributed into a completely randomized design. Treatments consisted of diets containing by-products with 70% of concentrate and 30% of tifton hay (Cynodon spp.) and were termed SM: control with soybean meal; SC: formulated with soybean cake; SUC: formulated with sunflower cake and PC: formulated with peanut cake. Diets had no effects on the carcass traits evaluated. There was no significant effect on the mean values of perirenal, omental and mesenteric fats (0.267, 0.552 and 0.470 kg, respectively) and there was no influence on the percentages of moisture, ether extract, crude protein or ash in the loin between experimental diets. Diets containing by-products from the processing of oil seeds did not change fatty acids found in lamb meat. The use of by-products from oil seeds provided similar carcass and meat traits, thus their use can be recommended as eventual protein and energy sources for feedlot lambs.